Pelatihan Kegiatan Membuat Keterampilan Mozaik Dengan Palawija Untuk Meningkatkan Kreativitas Siswa Kelas V SDN 104277 Desa Tanah Merah - Juli Yanti Harahap; Diva Friska; Indah Sekar Wangi; Siti Asnik Kumala Sari; Yulia Anjani; Hania Abidah (Journal on Education, 2024)
Community Service with the title "Training in Activities for Making Mosaic Skills with Secondary Education to Increase the Creativity of Class V Students at SDN 104277 Tanah Merah Village" aims to increase students' creativity in making skills in the form of mosaics. The method used in community service activities is through the lecture method and providing training to class V students at SDN 104277 Tanah Merah Village. This activity begins by providing tools and materials for mosaics using secondary crops such as peanuts, corn, green beans and rice. The results achieved from this mosaic training activity were that almost all students were able to increase their creativity in mosaic making skills and they were also able to make wall decorations using mosaic techniques.